2009
DOI: 10.2304/eerj.2009.8.4.497
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomized Metaphors and Young People's Educational Routes

Abstract: Drawing from an ethnographically grounded longitudinal study on educational transitions, the aim of this article is to analyse young people's reflections about their educational choices at different ages. Consistencies and breaks in their plans and actual choices are explored and reflected in relation to the economic, social, cultural and emotional resources they possess. In particular, the author explores taken-for-granted dichotomous metaphors that seem to open up certain educational routes and close others,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
(21 reference statements)
1
15
0
5
Order By: Relevance
“…However, recent research has highlighted variations within this group, which is actually very heterogeneous, and found that quite a large proportion of the boys consider their academic learning to be important (Abraham 2008;Hallam and Ireson 2006). The subject of our text is this recent finding, and how the young men attending the researched programmes constructed themselves (and were constructed) as practical rather than theoretical, in accordance with the way working class men are traditionally represented and constructed (see also Brockmann 2010;Colley et al 2003;Lahelma 2009). However, our data indicate that dichotomies like this are not necessarily pronounced, and that theory and practice could be better integrated in ways that reduce young men's resistance to general education within vocational programmes.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, recent research has highlighted variations within this group, which is actually very heterogeneous, and found that quite a large proportion of the boys consider their academic learning to be important (Abraham 2008;Hallam and Ireson 2006). The subject of our text is this recent finding, and how the young men attending the researched programmes constructed themselves (and were constructed) as practical rather than theoretical, in accordance with the way working class men are traditionally represented and constructed (see also Brockmann 2010;Colley et al 2003;Lahelma 2009). However, our data indicate that dichotomies like this are not necessarily pronounced, and that theory and practice could be better integrated in ways that reduce young men's resistance to general education within vocational programmes.…”
Section: Introductionmentioning
confidence: 75%
“…As highlighted in several previous studies, manual, physical work is often placed in opposition to academic 'headwork' (e.g. Lahelma 2009;Willis 1977). A difference here is that while the students expressed a positive attitude towards work seen as traditional working-class labour, they were very aware of changes in the labour market, and that it would probably be very difficult for them to get the type of work they really wanted.…”
Section: Journal Of Vocational Education and Training 449mentioning
confidence: 96%
“…Por un lado, la evidencia demuestra que existen atribuciones de prestigio e idoneidad que tienden a vincular mejores resultados académicos en la etapa obligatoria con una mayor aptitud para seguir con el itinerario académico, y peores resultados académicos con facilidades para realizar tareas manuales. En este sentido, las habilidades manuales se vinculan al campo de conocimiento propio de las clases trabajadoras, mientras que las habilidades intelectuales se relacionan con las clases medias (Lahelma, 2009). En clave de género, Lappalainen et al (2013) incorporan las prácticas de orientación -y sus supuestos-al análisis de las elecciones educativas.…”
Section: Cambios Y Continuidades En Las Trayectorias Vitales Y Educatunclassified
“…En segundo lugar, es necesario considerar los procesos que se desarrollan dentro de cada institución educativa, tanto en la secundaria obligatoria como en la posobligatoria, pues sus órdenes escolares tienen efectos sobre lo que aspiran y esperan los y las jóvenes. Como sugieren los resultados de este trabajo, y como recoge ampliamente la literatura en el campo de las transiciones y de las trayectorias educativas (Lahelma, 2009;Walther et al, 2015), la institución escolar es un espacio central en la (re)producción de patrones de clase, género y origen migratorio. En este contexto, el papel de docentes y profesionales de la orientación es clave para entender cómo se «enfrían» 8 las expectativas y las aspiraciones del alumnado.…”
Section: Conclusiónunclassified
“…While VET's relationship with HE has been ambiguous and contested, VET has often been perceived as a choice for less ambitious youths or for those with lower career expectations (see, e.g., Silver and Brennan, 1988;Lahelma, 2009;Brunila et al, 2011). On the one hand, the opportunity to progress to HE has improved VET's status in Finland and Sweden since the 1990s, but not without those in favour of it having faced opposing policy discussions (Virolainen and Persson Thunqvist, 2017).…”
mentioning
confidence: 99%